2017
DOI: 10.29252/ijrm.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The putative effects of D-Aspartic acid on blood testosterone levels: A systematic review

Abstract: Background: D-Aspartic acid (D-Asp) is in invertebrate and vertebrate neuroendocrine tissues, where it carries out important physiological functions. Recently, it has been reported that D-Asp is involved in the synthesis and release of testosterone and is assumed can be used as a testosterone booster for infertile men, and by athletes to increase muscle mass and strength. Objective: The aim of this review is to summarize available evidence related to the effects of D-Asp on serum testosterone levels. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 54 publications
(68 reference statements)
1
27
0
Order By: Relevance
“…We hypothesize that this result may depend on the short duration of the treatment with D-Asp, being 4 weeks probably insufficient to induce significant clinical effects that could be detected. The improvement of fatigue, however, may be interpreted both as an effect of increased corticospinal excitability 24 or as an effect of D-Asp on testosterone levels 25,26 and muscle mass. 27…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this result may depend on the short duration of the treatment with D-Asp, being 4 weeks probably insufficient to induce significant clinical effects that could be detected. The improvement of fatigue, however, may be interpreted both as an effect of increased corticospinal excitability 24 or as an effect of D-Asp on testosterone levels 25,26 and muscle mass. 27…”
Section: Discussionmentioning
confidence: 99%
“…In addition to d -Ser, d -Asp appears to play a fundamental role in neurotransmission and in the neuroendocrine system, as indicated by both rodent and human studies [95,96,97]. d -Asp has been detected in multiple areas of the human brain (including the hippocampus and prefrontal cortex) and in (neuro)endocrine organs such as the adrenal gland, the pituitary gland, and the testis [39]. d -Asp levels in the nervous system increase during development, but decrease during postnatal stages [98].…”
Section: Physiological Roles Of D-amino Acidsmentioning
confidence: 99%
“…d -Asp has also been suggested to be involved in NMDA receptor-linked neurotransmission and related diseases [37]. Furthermore, d -Asp might play an important role in the development of the central nervous system and in the regulation of (neuro) endocrine processes, including the release of gonadotropin-releasing hormone (GnRH), growth hormone (GH), and testosterone [38,39]. However, these (neuro) endocrine effects of d -Asp have predominantly been established in rat studies, whereas human studies are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the important roles of AAs in a wide variety of pathophysiological events, we evaluated our findings, focusing only on men with either normospermia or oligozoospermia, and found significantly lower levels of alanine and tryptophan in men with lower motility rates, and lower levels of aspartic acid and glutamic acid in men with higher abnormal morphology rates. To date, a number of studies have reported the effects of these four AAs on sperm function (8,11,14,15,(19)(20)(21)(22)(23)(24). For example, in vitro motility, longevity, and in vivo fertility were enhanced in bull spermatozoa by tryptophan supplementation (11), while oral administration of aspartic acid resulted in the improvement of sperm quality and fertility using a rooster model (20).…”
Section: Discussionmentioning
confidence: 99%